Pengecekan Berita Palsu untuk Mengukur Hoaks di Era Disrupsi Informasi - Adila, Isma; Afnan, Nayla; Armantari, Gayuh Ambeg (Tuturlogi: Journal of Southeast Asian Communication, 2021)
The spread of hoaxes on social media continues to occur in Indonesia because there is no gatekeeping process to maintain information reliability. Thus, the gatekeeping process is returned to social media users, who can create and disseminate the information. This study describes and classifies hoax information spread on social media using a content analysis approach with mimetic practices. This research uses a descriptive qualitative content analysis method to describe and classify hoaxes spread in Indonesia. This research uses dimensions of mimetic practice, namely content, form, and stance. This dimension is to analyze the hoax data that has been collected with documentation techniques. All hoax information to be investigated is taken from one of Tempo's fact-checking accounts, namely @tempo.cekfakta. The account has been certified by the International Network of Independent Fact-Checkers (IFCN) as well as Facebook's partner in its third-party fact-checking program in Indonesia.